Peningkatan Proses Pembelajaran Tematik Terpadu Tema 8 Dengan Model Problem Based Learning Kelas IV - Sevila, Sevila; Nasrul, Nasrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This study aims to describe the improvement of integrated thematic learning process theme 8 with the Problem Based Learning (PBL) model. The approach used is a qualitative and quantitative approach. The type of research is classroom action research (CAR). The techniques are used observation, tests and non-tests. The results of the research in terms of planning showed an increase from the first cycle, that is, the implementation of the steps contained in the lesson plan has been implemented in the implementation of increased learning in the second cycle, each of the steps in the lesson plan can be implemented. In the learning process, it can be seen that there is an increase in teacher activitys from the first cycle whose average achievement is 87.5% with a good category (B) increasing to 96,42% with a very good category (SB) in cycle II. Also seen an increase in the activity of students from the first cycle whose average achievement was 87.5% with a good category (B) increased to 96,42% with a very good category (SB) in the second cycle.